Optimization of temporal phase in multi-phase contrast-enhanced MRI for gross tumor volume determination in pancreatic cancer radiotherapy - Meng, Kangning; Guo, Yujie; Yin, Yong; Su, Ya; Wang, Lizhen; Wang, Ruozheng; Gong, Guanzhong (Translational Cancer Research, 2026)
Pancreatic cancer is characterized by an insidious onset and rapid progression, and the accurate determination of the gross tumor volume (GTV) constitutes a critical prerequisite for ensuring the efficacy of radiotherapy. Multiphase contrast-enhanced magnetic resonance imaging (CE-MRI) enables the dynamic visualization of tumor hemodynamic perfusion characteristics; however, the tissue discrimination capability varies substantially across different enhancement phases. To date, there is no universal consensus on the optimal imaging phase for GTV determination in pancreatic cancer. This study aimed to quantitatively analyze the differences in imaging and GTV determination of pancreatic cancer using multiphase CE-MRI, thereby providing a basis for selecting the optimal phase for GTV determination.